PERAN HELEN KELLER INTERNATIONAL DALAM PENANGGULANGAN GIZI BURUK DAN GANGGUAN PENGLIHATAN PADA ANAK DI INDONESIA DALAM KERANGKA RPJMN TAHUN 2015-2019 - Dita Indriani (2020)
This study discusses the role of Helen Keller International as an international non-govermental organization in efforts to tackle visual impairment and improvement of nutrition in children in the framework of the 2015-2019 RPJMN. Nutrition is one of the foundations of sustainable development. Nutrition is one of the most important factors in achieving a country's Human Development Index. In the 2015-2019 RPJMN the health development target set by the ministry of health in the 2015-2019 Strategic Plan is one of the indicators that is a top priority in improving the Community Health and Nutrition Status. However, Indonesia still has many malnutrition problems including edit, and impaired vision in children. This will certainly hinder the achievement of development targets in Indonesia which have been stated in the 2015-2019 RPJMN. In its application, national development certainly requires contributions from various parties, one of which is the International Non-Government Organizations. One of the INGOs chosen by the Indonesian Government in overcoming nutrition problems is Helen Keller International. Helen Keller International is an international non-governmental organization engaged in the improvement of education and health. The research method used is a qualitative method with a descriptive analysis approach. This research is supported by the Role theory and International Non-Government Organizations and the Health Threat concept to study the title of this research. The final results of this paper will try to show that in an effort to achieve development targets in the 2015-2019 RPJMN especially in the field of health, the government certainly requires contributions from various parties in this case Helen Keller International who took part in tackling the problem of malnutrition and research disorders in children as a manifestation of the achievement of national development by involving International Non-Governmental Organizations.